1992
DOI: 10.1136/jnnp.55.12.1150
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the soleus H-reflex during pedalling in normal humans and in patients with spinal spasticity.

Abstract: Soleus H-reflexes were recorded in 10 normal subjects and seven patients with spasticity caused by incomplete spinal cord injury while they pedalled on a stationary bicycle which had been modified to trigger electrical stimuli to the tibial nerve at eight precise points in the pedal cycle. Stimulus strength was adjusted to yield M-waves of constant amplitude at each pedal position. During active pedalling, all normal subjects showed modulation of the H-reflex with the amplitude being increased during the downs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 22 publications
4
18
0
Order By: Relevance
“…Several previous studies have reported a similar modulation of the SOL H reflex with the background EMG activity during bicycling as we have reported here (Brooke et al 1992;Boorman et al 1992). A basically similar modulation has also been observed in relation to treadmill walking and running (Capaday and Stein 1986;Crenna and Frigo 1987;Simonsen and DyhrePoulsen 1999).…”
Section: Modulation Of H Reflexes and Mepssupporting
confidence: 70%
See 2 more Smart Citations
“…Several previous studies have reported a similar modulation of the SOL H reflex with the background EMG activity during bicycling as we have reported here (Brooke et al 1992;Boorman et al 1992). A basically similar modulation has also been observed in relation to treadmill walking and running (Capaday and Stein 1986;Crenna and Frigo 1987;Simonsen and DyhrePoulsen 1999).…”
Section: Modulation Of H Reflexes and Mepssupporting
confidence: 70%
“…Comparison of H reflexes and MEPs is commonly used either to provide evidence of changes in cortical excitability in relation to fatigue (Brasil-Neto et al 1993a) and plasticity (Brasil-Neto et al 1993b;Schiepatti et al 1996) or alternatively to provide evidence of changes in presynaptic inhibition of Ia afferents (Berardelli et al 1987). The reasoning behind this is that the H reflex and MEP are both assumed to be mainly monosynaptic in origin and to activate the same population of motoneurons.…”
Section: Comparison Of H Reflexes and Mepsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that passive lower-leg motion, such as cycling, stepping, and ankle joint movement, can induce H-reflex modulation, which depends on the sensory input due to the passive joint motions (Boorman et al, 1992;Brooke et al, 1995;Misiaszek et al, 1995;Pinniger et al, 2001). The results of this study further revealed that the sensory information accompanied with a passive upright posture is capable of modulating both the H-reflex and stretch reflex excitability of the soleus muscle.…”
Section: Functional Implicationsupporting
confidence: 57%
“…Previous reports have shown that the soleus muscle is activated during flexion of the foot (Houlé et al, 1999). In humans, the soleus muscle, which is also activated during flexion when pedaling, has been shown to be much smaller during passive than during active cycling, which requires force generation (Boorman et al, 1992). In these conditions, it is unlikely that much loading occurs during our bicycle training paradigm.…”
Section: Restoration Of Frequency-dependent Depression Is Not Load-dementioning
confidence: 80%